2008
DOI: 10.1128/jcm.00692-08
|View full text |Cite
|
Sign up to set email alerts
|

Changing Patterns in Frequency of Recovery of Five Methicillin-Resistant Staphylococcus aureus Clones in Portuguese Hospitals: Surveillance over a 16-Year Period

Abstract: A total of 629 nonduplicate methicillin-resistant Staphylococcus aureus MRSA isolates were recovered between June and November 2006 from 11 hospitals located in different areas of Portugal. Selected isolates (n ‫؍‬ 271, 43%) were typed by pulsed-field gel electrophoresis (PFGE), representatives of which were additionally characterized by spa typing, multilocus sequence typing, staphylococcal cassette chromosome mec (SCCmec) typing, and the presence of Panton-Valentine leukocidin (PVL). The 271 isolates were cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
90
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 52 publications
(42 reference statements)
8
90
1
Order By: Relevance
“…This report was later confirmed by Aires de Sousa et al (1), who described that the majority of isolates (54%) recovered from 11 Portuguese hospitals belonged to EMRSA-15. Interestingly, in the same report, the New York/Japan clone (ST5-SCCmec II), first detected in a Portuguese hospital in 2005 (a single isolate), and the Hungarian/Brazilian clone shared the same overall prevalence (17%), but the New York/Japan clone prevailed among hospitals in Lisbon, Portugal (1). In the present study, a similar coexistence of these three clones was observed among Portuguese MRSA isolates; however, the New York/Japan clone was the dominant clone, consisting of 29.2% of all isolates (18.8% of EMRSA-15 isolates).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This report was later confirmed by Aires de Sousa et al (1), who described that the majority of isolates (54%) recovered from 11 Portuguese hospitals belonged to EMRSA-15. Interestingly, in the same report, the New York/Japan clone (ST5-SCCmec II), first detected in a Portuguese hospital in 2005 (a single isolate), and the Hungarian/Brazilian clone shared the same overall prevalence (17%), but the New York/Japan clone prevailed among hospitals in Lisbon, Portugal (1). In the present study, a similar coexistence of these three clones was observed among Portuguese MRSA isolates; however, the New York/Japan clone was the dominant clone, consisting of 29.2% of all isolates (18.8% of EMRSA-15 isolates).…”
Section: Discussionsupporting
confidence: 70%
“…During the last few decades, methicillin-resistant Staphylococcus aureus (MRSA) has been a worldwide clinical problem and has increasingly been responsible for infections in both the community and hospital settings (1). This remarkable pathogen has acquired resistance to several classes of antimicrobial agents, therefore commonly exhibiting the multidrug resistance (MDR) phenotype, which poses a continuous threat for antimicrobial therapy (11,14).…”
mentioning
confidence: 99%
“…Nevertheless, since it was recovered from a periumbilical exudate of a neonate, the connection to the nosocomial setting could not be discarded, as ST80 PVLpositive isolates were already described as nosocomial isolates in the late 1990s [33]. Regular surveillance studies in Portuguese hospitals [34], together with the present study, seem to indicate that CA-MRSA-ST80 is not widely spread in Portugal in contrast to what was described in several other European countries [21,35].…”
mentioning
confidence: 49%
“…The human EMRSA-15 epidemic has also spread into the companion animal population [22,23], with veterinary hospitals also being healthcare settings that may experience high levels of transmission [24]. A c c e p t e d M a n u s c r i p t 12 documented in Portugal, Singapore and Australia [25][26][27]. One feature that may contribute to its success is the SCCmec IV element that this clone carries, which has a lower fitness cost than the larger SCCmec elements such as SCCmec types II and III that were prevalent in earlier HA-MRSA clones [28].…”
Section: Hospital-associated Meticillin-resistantmentioning
confidence: 99%